Modelling the structural changes sources of the Malaysian economy: I-O model - Bekhet H.A.; Yasmin T. (Inderscience Publishers, 2023)
The study explores the structural change in intermediate demand and total output for Malaysia economy through the changes in the input coefficient and Leontief inverse matrices for the period 1980 to 2013. Decomposition structural method was utilised to focus on changes in the economic structure with different levels of development over time. The economic structure is decomposed into three initial components (technology, intermediate and total output). The results show a rather remarkable degree of commonality in the patterns of growth processes, with more significant deviations between sectors compared to tables. Nevertheless, most changes within the sectors, and the Malaysian I-O table as a whole, seem to result from changes in the level of the efficiency. Technical relationship seems to have remained relatively unchanged. It seems that the economy has not moved fast enough forward, and does not seem to be oriented by, the type of exports that may sustain a dynamic industrial development, based on external markets. Copyright 2015 Inderscience Enterprises Ltd.